Roles of Re-entrant cluster glass state and spin-lattice coupling in magneto-dielectric behavior of giant dielectric double perovskite La1.8Pr0.2CoFeO6 - Singh P.; Alam M.; Kumar S.; Anand K.; Gangwar V.K.; Ghosh S.; Sawada M.; Shimada K.; Singh R.K.; Ghosh A.K.; Chatterjee S. (My University, 2025)
La based Co-Fe combined double perovskite (La1.8Pr0.2CoFeO6) was synthesized and the dielectric (zero-field and in-field), magnetic, X-ray absorption and Raman spectroscopy measurements have been investigated for La1.8Pr0.2CoFeO6 double perovskite. The existence of re-entrant cluster glass state is observed. The magneto-dielectric (MD) is found in two temperature regions (25-80 K and 125-275 K). It has been demonstrated that the observed MD at low and high temperatures are respectively due to the spin freezing and the spin-lattice coupling. Furthermore, the very large dielectric constant and the low loss suggest that La1.8Pr0.2CoFeO6 is very important from the application point of view. © 2020 IOP Publishing Ltd.